Model Pendidikan Karakter dengan Pendekatan Pembiasaan (Habit Forming) : Studi Kasus Model Pembiasaan Dengan Kegiatan Religi di MA Sultan Agung Kecamatan Sukolilo Kabupaten Pati - Masudatik, Mamik (Pascasarjana IAIN Kudus, 2022)
The aims of this study were to find out: (1) the character building model with a habit forming approach at Madrasah Aliyah Sultan Agung, Sukolilo sub-district, Pati district, (2) the habit forming approach at Madrasah Aliyah Sultan Agung, Sukolilo sub-district. Pati district, (3) the results obtained from the character education model with a habit forming approach in Madrasah Aliyah Sultan Agung, Sukolilo sub-district, Pati district. This research uses descriptive qualitative method. The data sources used are primary sources and secondary sources. Data collection techniques used observation, guided interviews and documentation. Based on the results of study, it can be concluded: (1) character building in MA Sultan Agung is carried out using a habituation approach, integrated extracurricular activities, integrated subjects, and environmental conditioning. (2) The habituation approach is programmed in the implementation of religious activities, assigning tasks and commendable behavior. (3) The direct results obtained from the character education model with a habit forming approach are the stronger the attitude of students' responsibility, the stronger tolerance between students and the low recapitulation of student violation scores (PPS). Indirect results obtained from the character building model with a habit forming approach are able to interact well in the community and increase in madrasa students of Aliyah Sultan Agung who was accepted in several good colleges. Keywords: Character building, habit forming approach, religious activities, MA Sultan Agung.